Luteolin promotes macrophage-mediated phagocytosis by inhibiting CD47 pyroglutamation - Zhiqiang Li (Translational Oncology, 2021)
‘Don't eat me’ signal of CD47 is activated via its interaction with SIRPα protein on myeloid cells, especially phagocytic cells, and prevents malignant cells from anti-tumor immunity in which pyroglutamate modification of CD47 by glutaminyl-peptide cyclotransferase-like protein (isoQC) takes an important part evidenced by our previous report that isoQC is an essential regulator for CD47-SIRPα axis with a strong inhibition on macrophage-mediated phagoctyosis. Therefore, we screened for potential isoQC inhibitors by fluorescence-activated cell sorting assay and identified luteolin as a potent compound that blocked the pyroglutamation of CD47 by isoQC. We further demonstrated that luteolin directly bound to isoQC using pull-down assay and isothermal calorimetric (ITC) assay. In consistency, we showed that luteolin markedly abrogated the cell-surface interaction between CD47 and SIRPα in multiple myeloma H929 cells and consequently promoted the macrophage-mediated phagocytosis. Collectively, our study discovered a promising lead compound targeting isoQC, luteolin, which functions distinctly from current CD47 antibody-based drugs and therefore may potentially overcome the clinical side effects associated with CD47 antibody treatment-induced anemia.